The Influence of Workload and Job Stress on the Employee Performance of Final Inspection Division of PT. Kyosha Indonesia : Workload, Job Stress and Employee Performance - Saputra, Redy Adhi (STIE Tri Bhakti, 2025)
This study aims to analyze the influence of workload and work stress on the performance of employees of the final inspection division partially and simultaneously at PT Kyosha Indonesia. The population and sample in this study amounted to 39 people using the saturated sampling technique method, this technique was used to determine the sample where all members of the population were sampled. In this study, multiple linear regression analysis was used. Partially, the workload variable has a positive and significant effect on employee performance variables. Partially, the variable of work stress has a positive effect on the insignificant variable of employee performance. Simultaneously, independent variables, namely workload variables and work stress, have a significant effect on the dependent variable, namely employee performance variables. The results of this study provide important insights for the management of PT Kyosha Indonesia in designing a more effective workload and work stress management strategy to improve the welfare and performance of employees of the final inspection division.